2022
DOI: 10.3390/pr10040637
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Growth Law of Multi-Fracture during Temporary Plugging Fracturing within a Stage of Multi-Cluster in a Horizontal Well

Abstract: Temporary plugging fracturing in a horizontal well with multi-stages and multi-clusters is usually used to improve stimulation efficiency and increase the gas production from shale gas reservoirs. However, the fracture propagation geometry and the mechanism of temporary plugging are still unclear, which restricts the further optimization of temporary plugging fracturing scheme. In this study, taking the Longmaxi shale as the research object and considering the intrafracture and intrastage temporary plugging, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They found that effective temporary plugging can be achieved by using a temporary plugging agent with the proper size and concentration. Li et al [2] also studied the fracture growth mechanism of diverting fracturing. They found that increasing the proportion of the temporary plugging agent of larger particle size can improve the effectiveness of intra-fracture and intra-stage temporary plugging fracturing, and tends to open new fractures.…”
Section: Experiments For Hydraulic Fracture Growthmentioning
confidence: 99%
“…They found that effective temporary plugging can be achieved by using a temporary plugging agent with the proper size and concentration. Li et al [2] also studied the fracture growth mechanism of diverting fracturing. They found that increasing the proportion of the temporary plugging agent of larger particle size can improve the effectiveness of intra-fracture and intra-stage temporary plugging fracturing, and tends to open new fractures.…”
Section: Experiments For Hydraulic Fracture Growthmentioning
confidence: 99%
“…Li et al [16] conducted indoor multi-cluster temporary plugging fracturing experiments in horizontal shale wells; investigated in detail the effects of fracture spacing, the number of fractures, ground stress, and the type of injected fluids on the initiation of multi-cluster fractures; and quantitatively investigated the expansion pattern of multi-cluster fractures during the TPDF process. Li et al [17] proposed a new method of multi-stage and multi-cluster temporary plugging experiments in horizontal wells that considered fracture temporary plugging and segmented temporary plugging and investigated the effects of the particle size combinations of the plugging agent, its concentration, and the number of clusters at a certain stage on the geometry of fractures. Chen et al [18] developed a new thermo-responsive temporary plugging agent by conducting indoor tests that were successfully applied in the field, and the production and injection data in the field proved that the effect of production increase was remarkable.…”
Section: Introductionmentioning
confidence: 99%
“…To gain insights into the growth behavior of multi-fracture during TPDF, numerous studies have been conducted by scholars. These studies have revealed that the effectiveness of temporary plugging is influenced by factors such as geological conditions (e.g., horizontal differential principal stress ∆σ h , temperature, BPs, natural fractures, and induced stress of primary fractures) and operational parameters (e.g., type, particle size, concentration, and viscosity of plugging agents, as well as displacement of fracturing fluid) [1][2][3][4][5][6][7]. Different plugging positions result in different diversion fracture patterns.…”
Section: Introductionmentioning
confidence: 99%